Sentence Recall by Children With SLI Across Two Nonmainstream Dialects of English - Oetting, Janna B. (J Speech Lang Hear Res, 2016)
PURPOSE: The inability to accurately recall sentences has proven to be a clinical marker of specific language impairment (SLI); this task yields moderate-to-high levels of sensitivity and specificity. However, it is not yet known if these results hold for speakers of dialects whose nonmainstream grammatical productions overlap with those that are produced at high rates by children with SLI. METHOD: Using matched groups of 70 African American English speakers and 36 Southern White English speakers and dialect-strategic scoring, we examined children's sentence recall abilities as a function of their dialect and clinical status (SLI vs. typically developing [TD]). RESULTS: For both dialects, the SLI group earned lower sentence recall scores than the TD group with sensitivity and specificity values ranging from .80 to .94, depending on the analysis. Children with SLI, as compared with TD controls, manifested lower levels of verbatim recall, more ungrammatical recalls when the recall was not exact, and higher levels of error on targeted functional categories, especially those marking tense. CONCLUSION: When matched groups are examined and dialect-strategic scoring is used, sentence recall yields moderate-to-high levels of diagnostic accuracy to identify SLI within speakers of nonmainstream dialects of English.